A Study on Development Abilityof Fishery Economy in China Based on Factor Analysis. Issue 1 (June 2020) - Yu, Lei; Xu, Zhicang
Abstract: The thesis adopts the factor analysis method, taking 11 indicators reflecting the fishery economic development capacity as the research object, and measures the output capacity, input capacity and comprehensive development capacity of China's fishery economy from 2009 to 2018. The results show that the input capacity of the fishery economy is significantly higher than the output capacity of the fishery economy; the pulling effect of the input capacity of the fishery economy on the output capacity of the fishery economy varies from strong to weak; the speed gradually slowed down.